The XML handbook - Goldfarb, Charles F.; Prescod, Paul. (Upper Saddle River, NJ : Prentice Hall PTR, 2000)
The who, what, and why of XML. Middle-tier servers. E-commerce. Portals. Publishing. Content management. Content acquisition. Stylesheets. Navigation. XML and programming. XML tutorials. Related tutorials. Resources.
Keywords: Computer; XML; XML (Document markup language)